MEMBANGUN KARAKTER PEDULI LINGKUNGAN MELALUI PENANAMAN POHON SEBAGAI PENGHIJAUAN LINGKUNGAN DI DESA BOLANG KECAMATAN LEBAKWANGI - Holilah, Holilah; Januriana, Andi Moch; Hilman, Muhamad; Sukarna, Royan Habibie (Universitas Sultan Ageng Tirtayasa, 2022)
Reforestation is an effort to plant trees and plants in places that are considered to be able to growand develop these plants. the benefits of reforestation are preventing soil erosion, making airquality better, improving air quality, controlling climate, preventing flooding and making thescenery more beautiful and fresh. The role and function of fruit plants for the environment needs tobe socialized to the people of Bolang Village. This service activity aims to (1) build the characterof the community who cares about the environment through planting trees as reforestation of theenvironment. (2) socializing the role and function of fruit plants to the people of Bolang Village.The methods used are training in the form of socialization, procurement of facilities andinfrastructure, field assistance or fruit planting and evaluation. The planting activity as a greeningof the environment was carried out together in July 2022 which took place in Bolang Village,Lebak Wangi District, Serang Regency - Banten. In its implementation, this activity involved 25participants including students and the people of Bolang Village. Its implementation includes: (1)environmental cleaning activities in Bolang Village which will be used as a reforestation location,(2) fruit tree planting activities, and (3) fruit plant maintenance activities. The results of this treeplanting activity are planting seedlings of rambutan, jackfruit, water guava, longan and soursoptree seedlings each as many as 5 tree seedlings at several locations in Bolang Village on land thatrequires reforestation in Bolang Village.